Dynamic Subcarrier and Power Allocation with Proportional Rate Constraints for Multi-User Space-Time Block-Coded OFDM System - Jian Xu; Wonkyu Paik; Jongkyung Kim; Jong-Soo Seo (2007 IEEE 65th Vehicular Technology Conference - VTC2007-Spring, 2007)
This paper investigates the subcarrier and power allocation problem of multi-user space-time block coded OFDM systems with each subcarrier shared by two users. The objective is to maximize the total system capacity subject to the power and proportional rate constraints of each user. A low-complexity suboptimal algorithm that separates subcarrier allocation and power allocation is proposed. Simulation results show that the proposed resource allocation algorithm for space-time block coded OFDM can improve the capacity significantly with the same BER performance compared with static FDMA fixed allocation algorithm and the MIMO-OFDMA scheme in which each subcarrier is used only by one user. Furthermore, the more important point is that it can make the capacity be distributed more fairly, very close to the ideal rate constraints, among users than the scheme which maximizes the system capacity only.